Escape me if you can: how AI reshapes news organisations’ dependency on platform companies - Simon, FM (Taylor & Francis, 2023)
Platform companies play a crucial role in the creation, dissemination, and business of news. They are also central actors in artificial intelligence (AI) which has led some to argue that the increasing use of AI in journalism may heighten the news industry’s dependence on platform companies. This article evaluates this argument. Drawing on 121 interviews with news workers at 33 leading publishers in the US, UK, and Germany, as well as 31 expert interviews, and secondary material it finds that AI reshapes the dependency of publishers on platform companies by exacerbating existing dependencies in distribution and creating new dependencies in production. News organisations rely on platforms for AI for various reasons, such as high development costs, lack of resources, and varying visions over their mission. The findings show that while increasing dependence on platforms is acknowledged, there is disagreement over its extent and impact. The reliance on platforms’ AI shows isomorphic tendencies and potentially limits publishers’ autonomy.